HAZARD ANALYSIS OF HEAVY METALS BUILDUP IN THE DREGS OF BAKAJEBA RESERVOIR, PAIKORO, NIGER STATE, NIGERIA - HAMZAT, A; DAN-KISHIYA, A.S.; IDOWU, R.T.; YUSUF, M.K.; LIMAN, A. B.; IBRAHIM, A.; YUSUF, N.O. (Nigerian Journal of Fisheries, 2023)
Bakajeba reservoir is a vital source of water for different needs in the region. Pollution from different sources may negatively affect the suitability and water quality of the reservoir. Accordingly, this study aimed to monitor changes in heavy metal buildup in dregs sampled monthly from the reservoir. Three sampling sites were selected for the study: S1, S2 and S3. The sediment samples were taken between November 2018 and October 2020 using the Ekman Grab. Samples collected were digested and analyzed for heavy metals, using an atomic absorption spectrophotometer for the summary and inductive statistics of the data. The results present lead, copper, zinc, iron, cadmium, and chromium concentrations with ranges as 0.33±0.13 - 0.38±0.02 mg kg-1, 0.28±0.17 - 0.39±0.03 mg kg-1, 0.17±0.02 - 0.24±0.04 mg kg-1, 0.24±0.01 - 0.39±0.03 mg kg-1, 0.42±0.07 - 0.49±0.0 mg kg 17, and 0.41±0.04 - 0.46±0.03 mg kg-1, respectively. Except for Zinc and iron, the concentration levels of other heavy metals in all stations exceeded the limits recommended by the FAO for domestic and aquaculture use. This suggests a degradation of ecological integrity and highlights an urgent need for restoration efforts.